2018
DOI: 10.1002/slct.201703133
|View full text |Cite
|
Sign up to set email alerts
|

Silsesquioxane‐Based Hexaphenylsilole‐Linked Hybrid Porous Polymer as an Effective Fluorescent Chemosensor for Metal Ions

Abstract: Silsesquioxane-based hexaphenylsilole-linked hybrid porous polymers (SHHPP-1, 2, and 3), prepared from one-step Friedel-Crafts reaction of octavinylsilsesquioxane (OVS) and 1, 1, 2, 3, 4, 5-hexaphenylsilole (HPS), have been investigated as potential sensors for heavy metal ions. The results of FTIR, solid state CP/ MAS NMR ( 13 C and 29 Si) and elemental analysis indicate that HPS unit has been successfully linked to the silsesquioxane framework. These hybrid porous polymers possess high surface areas and bimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Although various metal ions including Cu 2+ , Fe 3+ , Ni2+, Co 2+ , Zn 2+ , Mg 2+ , Cd 2+ , Al 3+ , Ag + , Hg 2+ , Mn 2+ , Pb 2+ , F − , Cl − , Br − , I − , HCO 3 − , S 2− , CO 3 2− , HPO 4 2− , SO 4 2− , NO 3 − and SO 3 2− (1.0×10 −3 mol L −1 ,V DMF :V water =5 : 5) were conducted, the emission signal did not clearly decrease compared with the blank group. However, the fluorescent emission signal realized 8 folds decrements and even quenched completely after the same amount of Ru 3+ was added, which revealed that TPAIE‐2 exhibited higher selectivity for Ru 3+ than many other composites reported . The result can be attributed to the electron transfer process from electron‐rich composites to Ru 3+ via electron transfer platform .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although various metal ions including Cu 2+ , Fe 3+ , Ni2+, Co 2+ , Zn 2+ , Mg 2+ , Cd 2+ , Al 3+ , Ag + , Hg 2+ , Mn 2+ , Pb 2+ , F − , Cl − , Br − , I − , HCO 3 − , S 2− , CO 3 2− , HPO 4 2− , SO 4 2− , NO 3 − and SO 3 2− (1.0×10 −3 mol L −1 ,V DMF :V water =5 : 5) were conducted, the emission signal did not clearly decrease compared with the blank group. However, the fluorescent emission signal realized 8 folds decrements and even quenched completely after the same amount of Ru 3+ was added, which revealed that TPAIE‐2 exhibited higher selectivity for Ru 3+ than many other composites reported . The result can be attributed to the electron transfer process from electron‐rich composites to Ru 3+ via electron transfer platform .…”
Section: Resultsmentioning
confidence: 91%
“…As a prominent example, octavinylsilsesquioxane (OVS) provides access to new cage compounds via functionalization wherein the excited state exists as a spherical LUMO in the cage center leading to novel photophysical properties . Very recently, several fluorescent hybrid porous materials based on OVS and conventional fluorophores have been reported . Unfortunately, these materials suffer from short emission wavelengths, small Stokes shifts and poor emission intensities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
in the chemical field, the application of porous materials is more extensive, such as catalysis, [18] ion exchange, [19] adsorption and separation, [20,21] sensing, [22,23] chromatography, [24] and energy storage. [25,26] The emergence of such new technological applications requires a higher level of control over the properties of porous materials and the need to create simple and efficient ways to prepare porous materials has steadily increased over recent years.Vinyl is an important substituent for the synthesis of many materials because it can carry out a variety of chemical reactions, including free radical polymerization, [27,28] anionic polymerization, [29] cationic polymerization, [30] Heck reaction, [31] Friedel-Crafts reaction and so on.
…”
mentioning
confidence: 99%
“…in the chemical field, the application of porous materials is more extensive, such as catalysis, [18] ion exchange, [19] adsorption and separation, [20,21] sensing, [22,23] chromatography, [24] and energy storage. [25,26] The emergence of such new technological applications requires a higher level of control over the properties of porous materials and the need to create simple and efficient ways to prepare porous materials has steadily increased over recent years.…”
mentioning
confidence: 99%